Kepentingan Ekonomi Politik Usaha Kecil di Malioboro, Yogyakarta [The Political Economy of Small Enterprises in Malioboro, Yogyakarta] - Muh Kamim, Anggalih Bayu (Jurnal Politica, 2023)
This study is aimed to explore the vulnerability of small enterprises in Malioboro that depend on mass tourism. The research question is how did the political economy of small enterprises in Malioboro change? Data collection was carried out by in-depth online interviews with small enterprise actors in Malioboro due to the Covid-19 pandemic situation. Data was also collected through searches of journal articles, manuscripts, government reports, online media reports, and books related to economic development of Malioboro. The results of the study show that the growth of small enterprises in Malioboro since the 18th century is related to the commodification of urban space around Pasar Gedhe. Massive development of urban infrastructure and the growth of tourism driven by the colonial government since the 19th century have encouraged the emergence of the "entrepreneurial city" phenomenon in Malioboro marked by the proliferation of small enterprises. The crisis in 1930 and the war for independence in 1945-1949 disrupted the economy in Malioboro, but did not kill small enterprises. After the 1970s, small enterprises grew and built organizations to sustain their livelihoods. Small businesses with their respective organizations seek to build connection with the ruling class to maintain their seasonal business. Small enterprises don't even hesitate to fight with each other. The clash of small enterprises is getting tougher after Malioboro’s revitalization project in 2016 to maintain the image of a tourist destination, for business continuity.AbstrakKajian ini bertujuan untuk menggali kerentanan usaha kecil di Malioboro yang bergantung pada turisme massal. Pertanyaan penelitian yang ingin dijawab adalah bagaimana perubahan ekonomi politik usaha kecil di Malioboro? Pengumpulan data dilakukan dengan wawancara mendalam secara daring kepada pelaku usaha kecil di Malioboro disebabkan situasi pandemi Covid-19. Data dikumpulkan pula melalui penelusuran atas artikel jurnal, manuskrip, laporan pemerintahan, pemberitaan media daring dan buku yang terkait dengan perkembangan ekonomi di Malioboro. Hasil kajian menunjukkan bahwa tumbuhnya usaha kecil di Malioboro sejak abad ke 18 berkaitan dengan komodifikasi ruang perkotaan dimulai di sekitar Pasar Gedhe dan berlanjut di sekitarnya. Pembangunan infrastruktur perkotaan secara masif dan tumbuhnya turisme didorong oleh pemerintah kolonial sejak abad ke-19 telah mendorong munculnya fenomena “kota wirausaha” di Malioboro ditandai dengan maraknya usaha kecil. Krisis tahun 1930 dan perang kemerdekaan tahun 1945-1949 sempat mengganggu perekonomian di Malioboro, tetapi tak serta merta mematikan usaha kecil. Pasca tahun 1970-an, usaha kecil semakin tumbuh dan membangun organisasi untuk mempertahankan penghidupannya. Usaha kecil dengan masing-masing organisasinya berupaya membangun koneksi dengan kelas penguasa untuk mempertahankan bisnisnya dalam menjaga usahanya yang bersifat musiman. Usaha kecil bahkan tak segan untuk berseteru dengan sesamanya dan semakin keras bertarung pasca penataan Malioboro pada tahun 2016 untuk menjaga citra destinasi wisata, demi keberlangsungan usaha.